The Prediction of a New CLCuD Epidemic in the Old World - Sattar, Muhammad N.; Iqbal, Zafar; Tahir, Muhammad N.; Ullah, Sami (Frontiers in Microbiology, 2017)
Cotton leaf curl disease (CLCuD), the most complex disease of cotton, is a major limiting biotic factor to worldwide cotton productivity. Several whitefly-transmitted monopartite begomoviruses causing CLCuD have been characterized and designated as CLCuD-associated begomoviruses (CABs). Despite of being reported over 100 years ago in Africa, CLCuD became economically pandemic causing massive losses to cotton production worldwide during past couple of decades. In Asia, cotton has faced two major epidemics during this period viz. “Multan epidemic” and “Burewala epidemic”. The “Multan epidemic” era was 1988-99 after which the virus remained calm until 2002 when “Burewala epidemic” broke into the cotton fields in Indo-Pak subcontinent, till 2013-14. However, both the epidemics were caused by monopartite begomovirus complex. Similarly in Africa, Cotton leaf curl Gezira virus with associated DNA-satellites causes CLCuD. Quite recently, in the Old World (both Asia and Africa), bipartite begomoviruses have started appearing in the areas under cotton cultivation. Under such aggravated circumstances, it seems we are heading towards another epidemic of CLCuD in the Old World. Here we articulate the causes and potential emergence of the third epidemic of CLCuD in Asia. The current situation of CLCuD in Asia and Africa is also discussed.